Abrocitinib for the treatment of atopic dermatitis. (2nd October 2020) - Crowley, Erika L.; Nezamololama, Novin; Papp, Kim; Gooderham, Melinda J.
ABSTRACT: Introduction: Janus kinase (JAK) inhibitors are emerging treatments in dermatology. Also known as JAKinibs, these agents target JAK-signal transducers and activators of transcription (JAK-STAT) pathway for intracellular signaling. Among the various immune-mediated inflammatory skin diseases that the JAK-STAT pathway plays a role in, atopic dermatitis (AD) is an important one. AD has a complex and multifactorial pathophysiology that is not fully understood. Immune dysregulation can result in epidermal barrier disruption and intensify atopic dermatitis. The newly developed abrocitinib (PF-04965842) selectively inhibits the JAK1 protein, which is believed to modulate cytokines involved in AD pathophysiology. Areas covered: This work is a review of the current literature related to abrocitinib, including the phase I, II, and III clinical trials, for the treatment of AD. Immunological considerations of abrocitinib and JAK inhibition are also explored. Expert opinion: Abrocitinib is among the first JAK inhibitors evaluated for the treatment of AD. Similar to other JAKinhibs that mechanistically block the signaling of several cytokines, abrocitinib possesses both positive and negative clinical attributes. Nonetheless, the risk-benefit profile of abrocitinib remains favorable. Up to 61% of AD patients achieve an EASI 75 response while a minority of responding patients experience mild to moderate symptoms related to tolerability.